2022
DOI: 10.1007/s44202-022-00023-9
|View full text |Cite
|
Sign up to set email alerts
|

Stoicism and death acceptance: integrating Stoic philosophy in cognitive behaviour therapy for death anxiety

Abstract: Growing empirical evidence has revealed the central role of death anxiety in numerous mental health conditions. Given this, there is a significant need for treatments which specifically address fears of death. Whilst such treatments have only recently been developed within clinical psychology, the discipline of philosophy has a long history of offering valuable perspectives on death which may ameliorate this fear. In particular, we propose that the philosophy of Stoicism, which originated in ancient Greece and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
0
8
0
1
Order By: Relevance
“…This promising finding highlights the need to target death anxiety using CBT‐based interventions, which specifically address the maladaptive beliefs (e.g. in contrast with helpful beliefs associated with neutral acceptance of death; Menzies & Whittle, 2022 ) and behaviours which maintain death anxiety (e.g. avoidance, argued to be the most common maladaptive coping strategy used for fears of death; McKenzie et al, 2017 ).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…This promising finding highlights the need to target death anxiety using CBT‐based interventions, which specifically address the maladaptive beliefs (e.g. in contrast with helpful beliefs associated with neutral acceptance of death; Menzies & Whittle, 2022 ) and behaviours which maintain death anxiety (e.g. avoidance, argued to be the most common maladaptive coping strategy used for fears of death; McKenzie et al, 2017 ).…”
Section: Introductionmentioning
confidence: 93%
“…Despite this, no psychometrically adequate measures of the construct exist • A measure of affect, beliefs and behaviours related to death anxiety was developed • Across three samples, items were refined and exploratory and confirmatory factor analyses were performed • The final 18-item measure showed good validity and reliability. It appears to be a useful clinical and research tool to assess death anxiety beliefs associated with neutral acceptance of death; Menzies & Whittle, 2022) and behaviours which maintain death anxiety (e.g. avoidance, argued to be the most common maladaptive coping strategy used for fears of death; McKenzie et al, 2017).…”
Section: Practitioner Pointsmentioning
confidence: 99%
“…According to (Balasubramanian et al, 2018) that the factors that contribute to preventing thanatophobia are high self-esteem, high religious beliefs, good health, sense of satisfaction in life, intimacy with family and friends, high fighting spirit. Furthermore (Menzies & Whittle, 2022) states that a person's fortitude can reduce death anxiety, where this fortitude is the basis of Cognitive Behavior Therapy and is a potential guide to the success of CBT. thanatophobia in respondents, in addition to being influenced by factors such as health conditions such as opportunistic infections that can cause death, also because most of the HIV patients who became respondents were homosexuals who had less religious beliefs.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive Behavior Therapy (CBT) is a psychotherapy that has been proven to be effective in overcoming anxiety in patients with chronic fatigue syndrome, overcoming insomnia, effectively reducing anxiety, and deprereducinganxietys with Chronic Obstructive Pulmonary Diseases. (COPD), reducing death anxiety in covid 19 Effectively incresersilience and acceptanresilienceth in individuals experiencing death anxiety (Menzies & Whittle, 2022) Furthermore (Menzies et al, 2021) developed an online CBT program to overcome death anxiety and showed significant results.…”
Section: A B S T R a Kmentioning
confidence: 99%
“…Isu kematian dan kekekalan ternyata masih terus mendapatkan perhatian dari para filsuf kontemporer dalam lanskap pemikiran filsafat kontemporer selama dua dekade terakhir (Andrade, n.d.;Bradley, Feldman, Johansson, 2012;Buben, 2022;Cholbi, 2016;Cholbi dan Timmerman, 2021;Farman, 2018;Knepper, Bregman, dan Gottschalk, 2019;Luper, 2009;Menzies & Whittle, 2022;Minerva, 2018;Palladino, 2016;Rojcewicz, 2021;Rothblatt, 2015;Scarre, 2007;Schumacher, 2010;Sisto, 2020;Stokes, 2021;von Verschuer, 2019) [ii].…”
Section: Pengantarunclassified